If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + (m + 2) + (m + 4) = 72 Reorder the terms: m + (2 + m) + (m + 4) = 72 Remove parenthesis around (2 + m) m + 2 + m + (m + 4) = 72 Reorder the terms: m + 2 + m + (4 + m) = 72 Remove parenthesis around (4 + m) m + 2 + m + 4 + m = 72 Reorder the terms: 2 + 4 + m + m + m = 72 Combine like terms: 2 + 4 = 6 6 + m + m + m = 72 Combine like terms: m + m = 2m 6 + 2m + m = 72 Combine like terms: 2m + m = 3m 6 + 3m = 72 Solving 6 + 3m = 72 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3m = 72 + -6 Combine like terms: 6 + -6 = 0 0 + 3m = 72 + -6 3m = 72 + -6 Combine like terms: 72 + -6 = 66 3m = 66 Divide each side by '3'. m = 22 Simplifying m = 22
| 9x+7=12x-5 | | 4c-3=2c+5 | | (x-8)(x+3)= | | 64-7k=-11k+8 | | -3x^2+19x-28=0 | | 2x^2+22x-48=0 | | -(5-t)=0[37t-12t+5(14+3t)] | | 2x^2+12=18 | | a+65=5a-15 | | 3(5w+15)=210 | | 5x-8y=1 | | f(1-2)= | | 5(x+3)=2(x+1) | | a-9a+75=135+2a | | -6z+8+4z=-3z+13 | | -8w+8-3w=2-6w+2 | | 11p+3p-15p=743 | | 8x-23=2x+2 | | n+(n+1)+(n+2)+(n+3)=-122 | | 7(x+5)-4=33-6x-2+13x | | 160+.40x=293.60 | | 4t-11=-1 | | 1.99s+(2.99*2s)+.15=40 | | 15-2(x+5)=25 | | 2+2+x=6 | | 2r-3=18 | | 11+2g=2g-(g-15) | | 3x+5=5y-8 | | w-1=5w+3w-8 | | 7p+11=3p | | 3+d=9-d | | 2(x+4)+(5x)=7(x+4)-5 |